2019
DOI: 10.4310/mrl.2019.v26.n5.a2
|View full text |Cite
|
Sign up to set email alerts
|

Khovanov homology detects the Hopf links

Abstract: We prove that any link in S 3 whose Khovanov homology is the same as that of a Hopf link must be isotopic to that Hopf link. This holds for both reduced and unreduced Khovanov homology, and with coefficients in either Z or Z/2Z. Khovanov homology [Kho00] associates to each link L ⊂ S 3 a bigraded group Kh * , * (L), whose graded Euler characteristic recovers the Jones polynomial V L (q), as well as a reduced variant Kh * , * red (L) [Kho03]. It is known to detect the unknot [KM11], the n-component unlink for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…In summary, we have shown that K is either the figure-eight knot or, up to mirroring, a genus-2, fibered, strongly quasi-positive knot with the same knot Floer homology as T (2,5). It remains to show that d = 0 in the first case and d = 2 in the second.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In summary, we have shown that K is either the figure-eight knot or, up to mirroring, a genus-2, fibered, strongly quasi-positive knot with the same knot Floer homology as T (2,5). It remains to show that d = 0 in the first case and d = 2 in the second.…”
mentioning
confidence: 80%
“…In 2010, Kronheimer and Mrowka used instanton gauge theory to prove that Khovanov homology detects the unknot [13]. In 2018, Baldwin and Sivek combined gauge theory with ideas from contact topology to prove that Khovanov homology detects the trefoils [1]. Until now, these were the only knots known to be detected by Khovanov homology, though there have been several additional results (most very recent) regarding detection of links whose components are unknots and trefoils; see Hedden–Ni [8], Batson–Seed [4], Baldwin–Sivek–Xie [2], Xie–Zhang [24, 25], Lipshitz–Sarkar [15], Martin [17] and Li–Xie–Zhang [14].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Kronheimer and Mrowka showed that Khovanov homology detects the unknot [14]. Khovanov homology is also known to detect the unlink [9] [6], the Hopf link [5], the trefoil [4], the connected sum of two Hopf links [22], the torus link T (2, 4) [22], and split links [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many other detection results of Khovanov homology have been obtained. It is now known that Khovanov homology detects the unlink [BS15,HN13], the trefoil [BS18], the Hopf link [BSX19], the forest of unknots [XZ19], the splitting of links [LS19], and the torus link T (2, 6) [Mar20].…”
Section: Introductionmentioning
confidence: 99%